Engineering Drawing Practice Part 2 . Recommendations For Dimensioning And Tolerancing Of Size BSI (BSI, 1985)
Covers methods for the dimensioning and tolerancing of drawings, application of surface texture requirements, and gives an interpretation of limits of size for the control of form. Introduces the principle of independency of tolerances of size and form